Changes in lower-limb biomechanics, soft tissue vibrations, and muscle activation during unanticipated bipedal landings - Zhang, S.; Fufu, W.; Liu, Y. (Journal of Human Kinetics, 2019)
We aimed to explore the biomechanical differences between the anticipated drop jump and unanticipated drop landing. Twelve male collegiate basketball players completed an anticipated drop jump and unanticipated drop landing with double legs from a height of 30 cm. Kinematics, impact force, soft tissue vibrations, and electromyographic (EMG) amplitudes of the dominant leg were collected simultaneously. The anticipated drop jump showed more flexed lower limbs during landing and increased range of motion compared to the unanticipated drop landing. The anticipated drop jump also had lower impact force, lesser soft tissue vibration, and a greater damp coefficient at the thigh muscles compared with the unanticipated drop landing. Significant increases in the EMG amplitudes of the tibialis anterior, lateral gastrocnemius, rectus femoris, and biceps femoris were observed in the anticipated drop jump during the pre/post-activation and downward phases. The anticipated drop jump presented more optimized landing posture control with more joint flexion, lower impact force, less soft tissue vibrations, and full preparation of muscle activations compared with the unanticipated drop landing.